Identification of possible Ser/Thr/Tyr phosphorylation sites in the fungal histidine kinase CaNik1p by peptide array technique - Mohammed El-Mowafy; Ursula Bilitewski (Faculty of Pharmacy, Cairo University, 2018)
CaNik1p is a histidine kinase (HK) that is present in Candida albicans. It was found to be a target for antifungal activities on the hyperosmotic glycerol pathway. The protein has two well-known phosphorylation sites (P-sites); His510 and Asp924, that were found to be crucial for maintaining the fungicidal sensitivity. Our previous work showed that the double mutated protein, in H510 and D924, was still possessing kinase activity. In this study, we aimed to identify additional possible P-sites in this HK. Therefore, we constructed a peptide array that covers the full length protein. Incubation of the purified His-tagged CaNik1p with the peptide array in the presence of radioactive ATP [γ-32P] revealed the possible P-sites in each peptide. We classified the peptides according to their intensities. Peptides bearing His510 and D924 showed either null or very weak intensities. The highest intensity was corresponding to the peptide containing the amino acid T994, while lower intensities were related mainly to serine and threonine residues and to lower extent to tyrosine amino acid. We could show for the first time the detection of additional P-sites in CaNik1p that might contribute in the signalling pathways of C. albicans. Moreover, the protocol used in this study allows for direct focusing and prediction of the possible Ser, Thr, and Tyr phosphoaccepting residues in the newly discovered kinases.